The Relationship between Parenting Patterns and the Use of Gadgets with Early Childhood Social Development in PAUD Nurul Asrori Betumping - Mahendra, Juandra Prisma; Marzoan, Lalu (JUPE : Jurnal Pendidikan Mandala, 2024)
In the era of globalization, the impact of technological progress is increasingly visible and increasing; One type of technology that children like is gadgets. The use of gadgets by children is generally associated with the behavior of adults or other family members who observe the games or videos available on the device in the hope that the child will become curious and not easily offended. The aim of this research is to analyze and describe: individual economic conditions, individual relationships with their environment, duration of gadget use, and social development of early childhood. This quantitative research method is descriptive. The number of samples that researchers used in this research was 100 respondents. The measuring instrument that researchers use is a measuring instrument that has been proven to meet validity and reliability standards. The analysis method in this research uses the SPSS type 16.0 application. Based on the results of the research that the researchers have conducted, the results obtained are that there is a relationship between parenting patterns and the use of gadgets and the social development of early childhood at the Nurul Asrori Betumping preschool.